1989
DOI: 10.1038/339191a0
|View full text |Cite
|
Sign up to set email alerts
|

Structural plasticity broadens the specificity of an engineered protease

Abstract: The substrate specificity of alpha-lytic protease has been changed dramatically, with a concomitant increase in activity, by replacing an active-site Met with Ala. The substrate specificity of both this mutant and another similar mutant are extraordinarily broad. X-ray crystallographic analysis shows that structural plasticity, a combination of alternate side-chain conformations and binding-site flexibility, allows both large and small substrates to be well accommodated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
117
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(123 citation statements)
references
References 25 publications
6
117
0
Order By: Relevance
“…Similar flexible binding sites were also observed when mutations were made in the ␣-lytic protease S 1 subsite. Crystallographic data of M192A and M213A ␣-lytic protease mutants, with and without substrate analogues bound, demonstrated that there were local changes in conformation to accommodate the various P 1 residues; consequently, the mutant appeared to have relaxed specificity (43). Furthermore, crystal structures of Savinase with a Gly substitution residue, Ile 107 , which is analogous to Glu 255 in Kex2, demonstrated that the Savinase S 4 subsite was structurally flexible.…”
Section: Figmentioning
confidence: 93%
“…Similar flexible binding sites were also observed when mutations were made in the ␣-lytic protease S 1 subsite. Crystallographic data of M192A and M213A ␣-lytic protease mutants, with and without substrate analogues bound, demonstrated that there were local changes in conformation to accommodate the various P 1 residues; consequently, the mutant appeared to have relaxed specificity (43). Furthermore, crystal structures of Savinase with a Gly substitution residue, Ile 107 , which is analogous to Glu 255 in Kex2, demonstrated that the Savinase S 4 subsite was structurally flexible.…”
Section: Figmentioning
confidence: 93%
“…Some proteases exhibit no promiscuity, whereas others are as promiscuous as the detoxification enzymes. Structural plasticity has been correlated with increased promiscuity in mutants of native proteases (48,49). Given that proteases share a highly conserved catalytic mechanism and yet display widely variable promiscuous behavior, they may serve as a useful system to study the structural and dynamic determinants of promiscuity.…”
Section: Discussionmentioning
confidence: 99%
“…The suppressor alleles could serve to relax some of the constraints imposed on the identity of splice-site residues, thereby allowing mutant as well as wild-type sequences to be utilized. In well-studied systems of protein-substrate recognition, mutations that permit a wider range of interactions have been observed to increase the flexibility of the binding interface or pocket (Bone et al 1989;Morton and Matthews 1995). Such effects are not limited to mutations at the site of binding, and, in fact, may occur at considerable distances (Mace et al 1995;Gutierrez et al 1998).…”
Section: A Role For Prp8 At the Spliceosomal Catalytic Corementioning
confidence: 99%